Peptide CyRL-QN15 accelerates hair regeneration in diabetic mice by binding to the Frizzled-7 receptor - Wu, Yu-Tong; Ru, Ze-Qiong; Peng, Ying; Fu, Zhe; Jia, Qiu-Ye; Kang, Zi-Jian; Li, Yuan-Sheng; Huang, Yu-Bing; Yin, Sai-Ge; Guo, Kun; Liu, Nai-Xin; Feng, Cheng-An; et al. (Dōngwùxué yánjiū, 2024)
Individuals with diabetes frequently face serious challenges, including delayed wound healing and increased risk of infection. Notably, the regeneration of hair follicles plays a crucial role in accelerating diabetic skin damage repair, reducing the risk of infection, and enhancing overall skin health. Research has predominantly emphasized the re-epithelialization of diabetic wounds, with a paucity of in-depth studies on hair follicle regeneration. In the current study, we explored the effects of a bioactive amphibian-derived peptide, CyRL. QN15, on promoting hair regeneration in a diabetic skin model. In vivo experiments demonstrated that local treatment with CyRL.QN15 not only accelerated wound healing of scalded skin on the backs of diabetic Kunming (KM) mice but also improved growth of damaged hair follicles. Additionally, back-shaved diabetic C57BL/6 mice showed a significant increase in the growth of newly formed hair after 28 days of continuous CyRL.QN15 treatment. Further analysis indicated that the hair-regenerating effects of CyRL.QN15 were closely associated with the proliferation and migration of hair follicle stem cells (HFSCs). CyRL.QN15 enhanced intracellular (3-catenin expression by binding to the Frizzled-7 receptor on the surface of HFSCs. The up-regulation in (3-catenin modulated the levels of downstream proteins, such as c-MYC, Cyclin D1, and Lef1, ultimately inducing hair regeneration. This study not only reveals the robust effects of the bioactive peptide CyRL.QN15 in hair follicle regeneration but also provides novel avenues for the development of more targeted and effective therapeutics for diabetic wound healing in the future.